2010
DOI: 10.1016/j.jvs.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic factors on outcome and hospital costs associated with femoropopliteal revascularization

Abstract: Income level correlates with advanced presentation, advanced age, and lack of statin use. Although primary assisted patency rate is not affected by income status, an increased cost-per-day of patency and inferior limb salvage is found in lower income patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
1
26
1
1
Order By: Relevance
“…Income above 100 percent of the federal poverty line was protective against limb loss in a small study of femoropopliteal revascularization patients (AOR 0.06, 95% CI 0.01–0.51, p<0.001). 51 Guagliardo et al found that SES was a significant predictor of appendiceal perforation (AP) for California pediatric patients, but not for New Yorkers. 52 While this area will certainly benefit from further study, Lee et al note that this potential inequality may be the manifestation of an access barrier.…”
Section: Methodsmentioning
confidence: 99%
“…Income above 100 percent of the federal poverty line was protective against limb loss in a small study of femoropopliteal revascularization patients (AOR 0.06, 95% CI 0.01–0.51, p<0.001). 51 Guagliardo et al found that SES was a significant predictor of appendiceal perforation (AP) for California pediatric patients, but not for New Yorkers. 52 While this area will certainly benefit from further study, Lee et al note that this potential inequality may be the manifestation of an access barrier.…”
Section: Methodsmentioning
confidence: 99%
“…31 Socioeconomic, gender, and racial factors strongly influence procedural safety and efficacy measures. [32][33][34] Categorization of these factors is possible using simple scoring systems for highest level of education and household income stratified by multiples of the federal poverty line. Full characterization of these factors will likely be outside of the scope of most device and modality-centric endovascular studies but is something for authors to consider, especially in large-scale longitudinal outcome studies.…”
Section: Patient Factorsmentioning
confidence: 99%
“…12 Additionally, patients with lower socioeconomic status based on median household income levels had an increased risk for readmission, likely due to lack of access to healthcare or receiving care at poor-quality hospitals. 13 …”
Section: Understanding Readmission Following Vascular Surgery: a Concmentioning
confidence: 99%